Screening of Lactic Acid Bacteria with antimicrobial property isolated from fermented foods - Momin, Marium (BRAC University, 2018)
This Thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017